Meningkatkan Kepercayaan Publik dan Reputasi Dewan Perwakilan Rakyat Melalui Program Parlemen Remaja - rendro dhani; devi sonia (Jurnal Ilmu Komunikasi, 2021)
Many surveys show that the level of public trust in the Indonesian parliament (DPR) often occupies the lowest position compared to other government institutions. This study aims the efforts of the PR Bureau of the DPR in organizing the Parlemen Remaja (the Youth Parliament) program as an attempt to improve public trust and reputation through political education for the younger generation, to understand better the reputation management and relationship management mechanisms applied by PR Bureau of the DPR. The research method using an evaluation was carried out using the reputation management theory and relationships management theory of political public relations. Data collection techniques were carried out through literature study and in-depth interviews. The findings indicate that the Youth Parliament program is considered helpful in increasing student interest in politics, providing opportunities to interact with the community, and can improve their perception of the DPR. Moreover, the students can be used as brand ambassadors for the DPR by endorsing the Indonesian parliament on social media and doing word of mouth in their social milieu. It can be concluded that the program is fruitful in increasing positive perceptions and bridging the relationship between the DPR and its key stakeholders, but it is not significant enough to increase public trust and the institution's reputation.